Analisis Wanprestasi dalam Pemenuhan Layanan Konser oleh Mecimapro: Studi Hukum Perdata - Shofa, Ghaziyah; Fauzhia, Ira; Rohmatin, Rifa (Indonesian Journal Publisher, 2026)
This study aims to analyze breach of contract in the fulfillment of concert services by Mecimapro from a civil law perspective, as well as the legal consequences for consumers. The method used in this study is a normative legal method with a legislative and case approach. The legal material consists of primary sources, including the Indonesian Civil Code and the Consumer Protection Law, as well as secondary sources such as law books and scientific journals. The results of the study show that the discrepancy between the promised concert services and their actual implementation can be legally categorized as a breach of contract. The legal consequences include the right of consumers to file claims for compensation, refunds, or other forms of restitution in accordance with applicable laws. Therefore, concert organizers are legally responsible for consumer losses in order to ensure legal certainty and consumer protection.